The use of eucalyptol in Dentistry (Research, Society and Development, 2023)
Eucalyptol is obtained from the essence of eucalyptus or other producing sources. It is a clear, colorless liquid, of aromatic odor, camphoraceous, characteristic, with spicy flavor, followed by the feeling of freshness. Eucalyptol, widely used by the dental class, is an essential oil considered low toxicity and has a good dissolution ability on guta-pug cones. Given this, the present study aimed to conduct a study on the use of eucalyptol in dentistry, presenting its general aspects and indications and contraindications. For this, this research was based on a descriptive bibliographic review, which was based on scientific papers already published between 2018 and 2022 in Portuguese and specifically dealt with the proposed theme. Data collection took place on database, such as Google Academic, Scielo, Pubmed and Lilacs, resulting in the 18 scientific works analyzed and disclosed throughout this study. In the results found, it was clear that given the importance it has for the solvency of Guta-Percha, the eucalyptol in dentistry is widely used. For this reason, clinical studies have concluded that eucalyptol is considered a viable alternative to replace other solvents, as it is less annoying, has antibacterial activity, better odor, and unlike others, it is biocompatible and safe.